Halogenation Generates Effective Modulators of Amyloid-Beta Aggregation and Neurotoxicity - Wong, H. Edward (Public Library of Science, 2013)
Halogenation of organic compounds plays diverse roles in biochemistry, including selective chemical modification of proteins and improved oral absorption/blood-brain barrier permeability of drug candidates. Moreover, halogenation of aromatic molecules greatly affects aromatic interaction-mediated self-assembly processes, including amyloid fibril formation. Perturbation of the aromatic interaction caused by halogenation of peptide building blocks is known to affect the morphology and other physical properties of the fibrillar structure. Consequently, in this article, we investigated the ability of halogenated ligands to modulate the self-assembly of amyloidogenic peptide/protein. As a model system, we chose amyloid-beta peptide (Aβ), which is implicated in Alzheimer’s disease, and a novel modulator of Aβ aggregation, erythrosine B (ERB). Considering that four halogen atoms are attached to the xanthene benzoate group in ERB, we hypothesized that halogenation of the xanthene benzoate plays a critical role in modulating Aβ aggregation and cytotoxicity. Therefore, we evaluated the modulating capacities of four ERB analogs containing different types and numbers of halogen atoms as well as fluorescein as a negative control. We found that fluorescein is not an effective modulator of Aβ aggregation and cytotoxicity. However, halogenation of either the xanthenes or benzoate ring of fluorescein substantially enhanced the inhibitory capacity on Aβ aggregation. Such Aβ aggregation inhibition by ERB analogs except rose bengal correlated well to the inhibition of Aβ cytotoxicity. To our knowledge, this is the first report demonstrating that halogenation of aromatic rings substantially enhance inhibitory capacities of small molecules on Aβ-associated neurotoxicity via Aβ aggregation modulation.